PENGARUH KEPATUHAN TERHADAP PELANGARAN PAJAK DAN PENYAJIAN TERHADAP PEMBAYARAN PAJAK ALAT TRANSPORTASI KENDARAAN - Rahayu Nugraheni Rachmawati; Eka Satria Wibawa (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
The objective is to determine the effect of compliance, on tax violations and the presentation of means of transportation to make tax payment transactions for vehicle transportation equipment. This research was conducted at SAMSAT Semarang City. The amount of data taken by the sample is 100 by collecting data. The search for the number of respondents was carried out by means of questions and answers, questionnaires. The results of this study, the data can be seen that the effect of compliance, on the violation of the Vehicle Transportation Tax to pay the vehicle tax at the Semarang City SAMSAT Office